Overcoming the Challenge: Assessing Reading and Writing Literacy in Fourth-Grade Students - Ni Nyoman Rediani; Bernadetha Risky Kaize; Herrio Tekdi Nainggolan (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: The research aims to assess fourth-grade students' reading and writing literacy. Understanding the literacy level in this age group is crucial for identifying areas requiring improvement and enhancing their skills. This study provides insights for educational enhancements. Methodology: The research utilized a quantitative descriptive research design involving 85 fourth-grade students as participants. Data collection methods included interviews, observations, and tests. The interactive data analysis model was applied, consisting of three essential stages: data reduction, data presentation, and concluding (verification). Main Findings: The findings from this study highlight a prevailing issue concerning the reading and writing literacy skills of students, indicating that the majority of students, over 55%, are categorized as having "Low" literacy skills, while 22.35% fall into the "Moderate" category. This concerning situation can impede the holistic development of students' abilities, necessitating prompt and effective intervention. Novelty/Originality of this study: This study is unique for its focus on evaluating the reading and writing literacy skills of fourth-grade students at Elementary School 2 Merauke. It provides valuable insights into literacy education challenges and opportunities within this context. Using an interactive data analysis model, the research comprehensively assesses the factors affecting students' literacy skills. The findings highlight the importance of addressing print awareness and vocabulary, fundamental aspects of early literacy development, and the need to enhance teaching methods, including practical media usage and using the immediate environment for improved learning.